An application of the SF-6D to create health values in Portuguese working age adults - Ferreira, Lara Noronha (2012)
Objectives : This study describes the health-related quality of life(HRQOL) of the Portuguese working age population and investigates sociodemographic differences. Methods : Subjects randomly selected from the working age population ( n =2,459) were assessed using the SF-36v2 and converted into the preference-based SF-6D. Results : The mean SF-6D utility value was 0.70 (range 0.63–0.73). The mean utility value was lower for the lower educational level than for the highest. Women, people living in rural areas and older adults reported lower levels of utility values. Non-parametric tests showed that health utility values were signifi cantly related to employment; unskilled manual workers reported utility values lower than non-manual workers. For different diseases, mean utility values ranged from 0.58 (sexual diseases) to 0.66 (hepatic conditions). Cluster analysis was adopted to classify individuals into three groups according to their answers to the SF-6D dimensions. Multinomial logit regression was used to detect sociodemographic characteristics affecting the probability of following each cluster pattern. This study yielded normative data by age and gender for the SF-6D. Conclusions: The authors conclude that SF-6D is an effective tool for measuring HRQOL in the community so that different population groups can be compared. The preference-based measure used seems to discriminate adequately across sociodemographic differences. These results allow a better understanding of the impact of sociodemographic variables on the burden of illness perception.